Il ritorno in Tema dell’addio. Su alcune poesie inedite di Milo De Angelis (ENTHYMEMA, 2020)
This study analyses some unedited poems by Milo De Angelis, published in anthologies or journals between 1990 and 2003, which prelude to Tema dell’addio (Theme of farewell; Mondadori, 2005), dedicated to his wife, the poet Giovanna Sicari. The comparison between these poems establishes the existing ties with previous publications and some passages which foreshadow his next one. In conclusion, the inquiry theorizes that these texts belong to a preliminary phase of the writing process, given the substantial continuity with his previous works, the yet unfocused presence of certain themes that will characterize Tema dell’addio, and the lacking influence (later more evident) of some poems by Sicari. In the move from these unedited poems to the book, subjects are further distinguished and his writing becomes more precise: essential conditions to enable De Angelis’ obsession with the theme of return to manifest itself.
Keywords: Milo De Angelis; Giovanni Sicari; Italian poetry; unpublished poetry; philology